Predictive models of the rheological properties and optimal water content in doughs: An application to ancient grain flours with different degrees of refining. (September 2018) - Cappelli, Alessio; Cini, Enrico; Guerrini, Lorenzo; Masella, Piernicola; Angeloni, Giulia; Parenti, Alessandro
Abstract: This paper evaluates the relationship between the rheological properties of doughs and the constituents of flours made from ancient grain. It also examines the effect of water on the rheological properties of doughs obtained with three types of flour (refined white flour, type 2 flour, and whole wheat flour) and the associated chemical and physical phenomena. A Chopin alveograph was used to take rheological measurements. Significant differences were found between doughs made with refined and unrefined flours. Tenacity, deformation energy, and the curve configuration ratio decreased as total water content increased, while the inverse trend was found for extensibility and the index of swelling. The analysis made it possible to develop a model to predict the rheological properties of doughs produced with refined and unrefined flours, if the starch, insoluble fiber, protein, and gluten content is known. Although, ancient grains are notorious for their poor technological properties, even a minimum improvement in rheological performances would contribute to satisfying the increasing demand for these products and facilitate their production, with positive returns for economies and biodiversity. Finally, level curves diagrams made it possible to identify the optimum water content of doughs corresponding to the technological properties of the required finished product. Graphical abstract: Image 1 Highlights: P, W, and P/L show a decreasing trend with an increase in total water content. G and L show an increasing trend with an increase in total water content. Flour constituents are good predictors of alveographic parameters. Explained variance by developed models ranged from R 2  = 0.78 (L) to R 2  = 0.90 (P). Total water content strongly influences the rheological properties of doughs.